Evolutionary perspectives in computer music - Reis, Cecília (2019)
This paper presents a brief overview of music evolution - western and non-western music - from its genesis to serialism and the Darmstadt school. Some mathematical aspects of music are then presented and confronted with music as a form of art. Some questions follow: are these two (very) distinct aspects compatible? Can computers be of real help in automatic composition? Evolutionaty Algorithms (EAs) - Genetic Algorithms (GAs), Genetic Programming (GP), Particle Swarm Optimization (PSO) and Ant Colony Optimization (ACO) - are then introduced and some results of GAs and GPs application to music generation are analysed. Variable fitness functions and PSO application seems a promising way to explore. However, what output should be envisaged? Should we expect that computer music sounds as human music, or should we look for a totally different way to explore and listen? How far can go computer creativity and in what direction?